Automatic statistical volume element modeling based on the unified topology model - Couture, Adrien; François, Vincent; Cuillière, Jean-Christophe; Pilvin, Philippe (International journal of solids and structures, 2020)
Needs for new particle based heterogeneous materials as led to the development of many Statistical Volume Element (SVE) modeling schemes tailored to specific shapes of particles or meshing procedures. To generalize the numerical analysis of particle filled SVEs, a modeling methodology based on the Unified Topology Model (UTM) is proposed. Using the concept of Boundary Representation (BRep) and a modified Random Sequential Adsorption (RSA) algorithm, the geometry of a Statistical Volume Element (SVE) can be generated automatically with any shape of particles. Using an integration of Computer-Aided Design (CAD) and mesh tools, a mesh size map is constructed with the objective of minimizing the number of mesh elements while preserving quality of the discretization. The SVE is meshed using proven CAD model meshing algorithms for a robust and reliable result. Simulation and post processing are carried out automatically, without any user interaction. To illustrate the potential of this new method, a short glass fiber / epoxy matrix composite is modeled with spherical and elongated cylindrical particles.